1974
DOI: 10.1177/003591577406701014
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to Metal Dental Plate

Abstract: M N, woman aged 64. Housewife History: Several years ago suffered from suspender-buckle dermatitis. August 1971: The patient acquired a chromealloy dental plate, and four weeks later was admitted to hospital with acute generalized eczema which responded well, but not completely, to treatment. Patch-testing confirmed sensitivity to nickel and cobalt. She continued to have a mild hand eczema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1980
1980
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Hypersensitive reactions due to nickel in the cobalt-chromium alloys of dentures have been described in the literature. The reactions reported are contact stomatitis (Deissler & Sheets, 1942;Wood, J974), dermatitis (Jakobs, 1953;Sidi, 1961;Brendlinger & Tarsitano, 1970;Glendenning, 1971;Fisher, 1974) and combinations of both local and general reactions (Levantine, 1974). With regard to the obviously unpleasant side-effects resulting from sensitivity to nickel it has been suggested that a nickel-free alloy should be used routinely in the casting of cobalt-chromium dentures (Wood, 1974).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypersensitive reactions due to nickel in the cobalt-chromium alloys of dentures have been described in the literature. The reactions reported are contact stomatitis (Deissler & Sheets, 1942;Wood, J974), dermatitis (Jakobs, 1953;Sidi, 1961;Brendlinger & Tarsitano, 1970;Glendenning, 1971;Fisher, 1974) and combinations of both local and general reactions (Levantine, 1974). With regard to the obviously unpleasant side-effects resulting from sensitivity to nickel it has been suggested that a nickel-free alloy should be used routinely in the casting of cobalt-chromium dentures (Wood, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…There are some reports in the literature where hypersensitive reactions to nickel in cobalt-chromium alloys are presented and discussed. The reactions reported vary from mucosal contact stomatitis to generalized dermatitis without any oral mucosal reaction (Deissler & Sheets, 1942;Jakobs, 1953;Sidi, 1961;Brendlinger & Tarsitano, 1970;Levantine, 1974;Wood, 1974). Magnusson et al (1979) showed with patch tests carried out on ten patients, with known nickel allergy, that the pure metal nickel and cobalt-chromium alloys containing nickel caused positive skin reactions which were especially pronounced for an alloy containing 9% nickel by weight.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 139 patients, 115 went into remission when the RPD was removed. Patients with denture stomatitis related to the metal part of the prosthesis, and who have been patch-tested for contact allergy to nickel, cobalt, and chromium, often react to two or all three of the metals (Re, 1960;Brendlinger and Tarsitano, 1970;Levantine, 1974;Wood, 1974;Kaaber etal, 1979). Fixed prosthodontic restorations made of steel (ironbased alloys with chromium and nickel) are extensively used in some East European countries.…”
Section: Reactions To Specific Alloy Systemsmentioning
confidence: 99%
“…Metal release from Co-Cr partial dentures has been desribed (Stenberg, 1982;Fontes de Melo, Gjerdet & Erichsen, 1983). Toxicological damage to patients due to tbis release is not likely (Bergman, 1977), but allergic reactions to cobalt, chrome (or nickel, as a minor addition) from Co-Cr dental appliances have been suggested (Brendlinger & Tarsitano, 197(J;Levantine, 1974;Bergman, 1977;Dooms-Goossens et ai, 1980). It was the aim of this investigation to assess the corrosion behaviour of a new Co-Cr-Mo alloy intended for use as a ceramic substrate.…”
Section: Introductionmentioning
confidence: 99%